A Holistic Approach to Enhancing MSME Performance - Fadila Khairani; Ana Fitria; Muhammad Syauqi Bin-Armia; Israk Ahmadsyah (Edunomics Journal, 2025)
This study investigates the impact of financial literacy, financial inclusion, and digital payment adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach with primary data collected through structured questionnaires, the analysis reveals that while not all individual variables show significant effects, together they contribute meaningfully to improving MSME performance. The findings suggest that financial literacy alone is not sufficient unless supported by access to finance, appropriate digital tools, and practical implementation strategies. This emphasizes the need for a more integrated approach in empowering MSMEs, involving training, simplified financial processes, and the use of financial technology